Optimalisasi Pembelajaran Pendidikan Islam di Sekolah/Madrasah Upaya dan Faktor Penghambat Pembelajaran Pendidikan Islam - Muhammad Anas Ma`arif (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACT The importance of optimizing the learning of Islamic education in the realm of formal institutions either in schools or in madrasah is a problem faced by related institutions. Development of strategies and learning models is always on the increase to support how learners can realize and apply what has been taught by educators. Some of the supporting factors and obstacles traversed by related institutions have always been challenges. In this case the government has also been supportive with various policies. Purpose-This study aims to describe and analyze the learning optimization of Islamic Religious Education in schools/madrasah an effort and obstacles in the implementation of Islamic education (PAI). Design/methodology/approach-This study uses literature research from the data of books that have been collected relevant to the theme. Findings- Optimization through internalization, development of school culture, integration in learning and development of Islamic education learning system design. Originality-. The optimization of learning of Islamic education in the realm of school/madarasah is done in various ways especially internalization, externalization and integration. Islamic education has always been the main focus in educating and developing the character of children. Keyword: Learning Optimization, Islamic Education, School / Madrasah Efforts